Mots, textes et images : tours de passe-passe dans les artist web projects d’Allen Ruppersberg et d’Iñaki Bonillas - Constance Moréteau (Itinéraires, 2018)
What would be the meaning of words when sleights of hand take place between the indexation of reality by photographing, the indexation of photographs by words making and the indexation of literary works by photographs? The two artist web projects produced by Allen Ruppersberg and Iñaki Bonillas raise such issues under the guise of access to their private archives.